Rare bird documentation form for Northern Goshawk at Big Creek Lake, 1981 - Robinson, John C., 1959-et al (1981)
Rare bird documentation form for a Northern Goshawk at Big Creek Lake in Polk County, IA on November 21, 1981. Epson - sheet feed